Servant Leadership: A Discussion between Managerial Competencies and Managerial Values - Agnieszka Postuła (Studia i Materiały)
Purpose: The goal of this article is explore the intricacies of servant leadership, the evolving expectations of new generations, the importance of managerial competencies and values, and the empirical findings from the comprehensive research conducted. This exploration aims to provide valuable insights into the multifaceted world of leadership and management in contemporary organizations.